PENGARUH RELEGIUSITAS TERHADAP AKHLAK REMAJA - Suharman Suharman (PAI RAFAH, 2020)
Research studies are motivated by researchers interest in the impact and influence of religiosity on adolescent morals. Due to the current declining adolescent morals, so the need for this study to see how much influence the religiosity of coaching and the formation of adolescent morals This study aims to determine whether there is an effect of regilisutas on adolescent morals. The type and approach of this study is research and quantitative approaches. The population used in this study were all students in SMA Negeri 5 Prabumulih. The sampling technique used in this study is the proportionate stratified random sampling technique which is part of the probability sampling technique. The data collection technique used is documentation and questionnaire. The results of the study can be concluded; first, the majority of parents of students of SMAN 5 Prabumulih (68.5%) applied permissive parenting, the level of interaction was mostly (71.8%) of students with peers in the medium category, the level of mass media exposure was mostly (66.4% ) students in the medium category, the level of religiosity was mostly (69.8%) students in the moderate category, and the morals of most (77.2%) students were rated by PAI teachers in the quite good category; second, the results of the analysis of the coefficient of determination shows that the good and bad character of adolescents can be directly influenced by parenting, peers, mass media, and religiosity by 6.6%. But partially, from the four factors only religiosity has a positive and significant direct effect on adolescent morals. This means that the higher the religiosity of adolescents, the better the morals will be. The results of the path coefficient analysis indicate that the magnitude of the influence of religiosity is 23.9%, while peers is 10.3%, parenting is 3.7%, and mass media is only 2.8%; Third, the results of the analysis of the coefficient of determination show that the level of adolescent religiosity is only able to be directly affected by parenting, peers, and mass media by 1%. Although not significant, the results of a partial analysis show that the magnitude of the influence of parenting on religiosity is 9%, the influence of peers on religiosity is 3.1%, and the influence of mass media on religiosity is only 2.3%.